Backstepping design for position tracking control of nonlinear system - Md. Rozali, S. (2012)
In ordinary feedback-based systems, the nonlinearities existing in the system is eliminated by using linearization method. However, backstepping method allows additional nonlinearities to be created and introduced to the control process so that the undesirable nonlinearities can be cancelled out from the system. In this work, electrohydraulic actuator system is taken as a numerical example. Backstepping controller is designed for the system without disturbance and with disturbance. The performance of the designed controller to the system without and with disturbance is observed through the tracking error.